2004
DOI: 10.2527/2004.8272140x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary trace mineral concentration and source (inorganic vs. chelated) on performance, mineral status, and fecal mineral excretion in pigs from weaning through finishing12

Abstract: Two hundred and sixteen weanling gilts (6.65+/-0.08 kg) were used to determine the effects of decreasing supplemental concentrations of Zn, Cu, Fe, and Mn, and trace mineral source (inorganic vs. chelated) on growth performance, mineral status, and fecal mineral concentrations from weaning through development. The study was conducted over three trials with 72 pigs in each trial. Gilts were blocked by weight and randomly assigned to either 1) control, 2) reduced inorganic, or 3) reduced chelated trace minerals.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

22
70
2
7

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(101 citation statements)
references
References 14 publications
22
70
2
7
Order By: Relevance
“…The results obtained are in accordance with those described by Creech et al (2004) with pigs in all the production stages, who also verified that animals fed diets with lower levels of inclusion of trace minerals inclusion presented lower excretion in feces.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…The results obtained are in accordance with those described by Creech et al (2004) with pigs in all the production stages, who also verified that animals fed diets with lower levels of inclusion of trace minerals inclusion presented lower excretion in feces.…”
Section: Resultssupporting
confidence: 91%
“…Similar results were verified by Creech et al (2004), in an experiment with pigs in the weaning and growth phases, fed controlled diets containing normal levels of inorganic minerals (Zn, Cu, Fe and Mn) or fed diets containing minerals from organic sources in reduced quantities, and no significant difference in the performance of the animals was verified. The possibility of reducing the level of inclusion of trace minerals in diets was also verified by Veum et al (1995), Fremaut (2003) and Burkett et al (2005), once better performance results of pigs were observed when the levels of addition of trace minerals was reduced in 50%, 30% and 50% in relation to the normal levels, respectively, considering an addition in the organic form, corroborating the results of the present investigation.…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…The presented results showed that the effect of humic substances from a diet on different trace elements was unequal. Potential antagonistic interactions, such as between iron and manganese or iron, copper and zinc etc should also be taken into consideration (Creech et al 2004). A high proportion of humic acids in water was associated with increased prevalence of thyroid dysfunctions in human population (Huang et al 1994).…”
Section: Resultsmentioning
confidence: 99%
“…The effects of MAC on growth performance were assessed by a host of researchers. Creech et al (2004) previously reported that trace mineral sources exerted no effects on performance during the growing or gilt development phase. Coffey et al (1994) and Zhou et al (1994) previously reported that additions of Cu from copper-lysine complexes resulted in improved pig performance as compared with copper sulphate.…”
Section: Statistical Analysesmentioning
confidence: 95%